Increased atmospheric SO₂ detected from changes in leaf physiognomy across the Triassic-Jurassic boundary interval of East Greenland. - Karen L Bacon; Claire M Belcher; Matthew Haworth; Jennifer C McElwain (PLoS ONE, 2013)
The Triassic-Jurassic boundary (Tr-J; ∼201 Ma) is marked by a doubling in the concentration of atmospheric CO2, rising temperatures, and ecosystem instability. This appears to have been driven by a major perturbation in the global carbon cycle due to massive volcanism in the Central Atlantic Magmatic Province. It is hypothesized that this volcanism also likely delivered sulphur dioxide (SO2) to the atmosphere. The role that SO2 may have played in leading to ecosystem instability at the time has not received much attention. To date, little direct evidence has been presented from the fossil record capable of implicating SO2 as a cause of plant extinctions at this time. In order to address this, we performed a physiognomic leaf analysis on well-preserved fossil leaves, including Ginkgoales, bennettites, and conifers from nine plant beds that span the Tr-J boundary at Astartekløft, East Greenland. The physiognomic responses of fossil taxa were compared to the leaf size and shape variations observed in nearest living equivalent taxa exposed to simulated palaeoatmospheric treatments in controlled environment chambers. The modern taxa showed a statistically significant increase in leaf roundness when fumigated with SO2. A similar increase in leaf roundness was also observed in the Tr-J fossil taxa immediately prior to a sudden decrease in their relative abundances at Astartekløft. This research reveals that increases in atmospheric SO2 can likely be traced in the fossil record by analyzing physiognomic changes in fossil leaves. A pattern of relative abundance decline following increased leaf roundness for all six fossil taxa investigated supports the hypothesis that SO2 had a significant role in Tr-J plant extinctions. This finding highlights that the role of SO2 in plant biodiversity declines across other major geological boundaries coinciding with global scale volcanism should be further explored using leaf physiognomy.